High Energetic Demand of Elite Rowing – Implications for Training and Nutrition - Winkert, Kay; Steinacker, Juergen M.; Koehler, Karsten; Treff, Gunnar (Frontiers in Physiology, 2022)
Purpose: Elite rowers have large body dimensions, a high metabolic capacity, and they realize high training loads. These factors suggest a high total energy requirement (TER), due to exercise energy expenditure (EEE) and high additional energetic needs. We aimed to study EEE and intensity related substrate utilization (SU) of rowers during rowing (EEEROW) and other (EEENON-ROW) training. Methods: We obtained indirect calorimetry data during incremental (N=174) and ramp test (N=42) ergometer rowing in 14 elite open-class male rowers (body mass 91.8 kg, 95% CI [87.7, 95.9]). Then we calculated EEEROW and SU within a three-intensity-zone model. To estimate EEENON-ROW, appropriate estimates of metabolic equivalents of task were applied. Based on these data, EEE, SU and TER were approximated for prototypical high-volume, high-intensity, and tapering training weeks. Data are arithmetic mean and 95% confidence interval (95% CI). Results: EEEROW for zone 1 to 3 ranging from 15.6 kcal∙min-1, 95% CI [14.8, 16.3] to 49.8 kcal∙min-1, 95% CI [48.1, 51.6], with carbohydrate utilization contributes from 46.4%, 95% CI [42.0, 50.8] to 100.0%, 95% CI [100.0, 100.0]. TER was estimated to be 6,775 kcal·day-1, 95% CI [6,651, 6,898], 5,772 kcal·day-1, 95% CI [5,644, 5,900], and 4,626 kcal∙day-1, 95% CI [4,481, 4,771] during a high-volume, a high-intensity, or a taper week, respectively. Conclusion: EEE in elite open-class male rowers is remarkably high already during zone 1 training and carbohydrates are dominantly utilized, indicating relatively high metabolic stress even during low intensity rowing training. During high-volume training weeks, TER is presumably at the upper end of the sustainable total energy expenditure during daily training conditions. Periodized nutrition seems warranted for rowers to avoid low energy availability, which may negatively impact performance, training, and health.